THE EFFECT OF TEACHER CREATIVITY IN DEVELOPING LEARNING MEDIA ON STUDENT LEARNING OUTCOME IN ISLAMIC EDUCATION SUBJECT AT SENIOR HIGH SCHOOL 2, MAKASSAR - Riska Ramadani (JICSA : Journal of Islamic Civilization in Southeast Asian, 2022)
The Effect of Teacher Creativity in Developing Learning Media on Student Learning Outcomes in the Pai Subject at SMA Negeri 2 Makassar. This study aims at examining teacher creativity in the Pai subject at SMAN 2 Makassar. The research method used in this study is quantitative, therefore the data collection technique uses observation, documentation, questionnaires, and interviews. Based on the results of the study, it proved that teacher creativity in PAI subjects at SMAN 2 Makassar was in the good category, namely at intervals of 31-35 with an average value of 32.92, while the learning media in PAI subjects at SMAN 2 Makassar were in the sufficient category, namely at intervals of 19-21 with an average score of 22.14, as well as student learning outcomes in PAI subjects at SMA Negeri 2 Makassar are in the good category at intervals of 26-28 with an average score of 22.97. From the results of the test, the count of teacher creativity in developing instructional media is 2.701 which is greater than the predetermined table value of 2.021. While the significant value is 0.029 <0.05. In addition, it is known that the regression equation with the formula Y = a + b1x1 + b2x2 = 13.606 + 0.069X1 + 0.316X2. Thus, it can be stated that there is an influence between teacher creativity in developing learning media on student learning outcomes in Pai subject at SMA Negeri 2 Makassar.